Penguatan Karakter Keislaman dan Penggalian Potensi Masyarakat: Studi Implementasi KKN STIBA Makassar di Desa Damai: Strengthening Islamic Character and Exploring Community Potential: A Study of the Implementation of KKN STIBA Makassar in Damai Village - Iskandar, Iskandar; Muhammad Fachmi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The VIII STIBA Makassar Real Work Lecture (KKN) Program in Damai Village, Maros Regency, South Sulawesi, in 2025 aims to strengthen the Islamic character of the community and optimize local potential. Using the Participatory Action Research (PAR) approach, students carry out various da'wah, educational, social and community empowerment activities. The results show increased religious participation, increased Al-Qur'an literacy, and strengthened social values. The main supporting factors are community openness and village government support. The main obstacle is limited time and resources. This study emphasizes the importance of integrating science, da'wah and community-based empowerment.